(untitled) (Indian Journal of Arid Horticulture, 2025)
A field experiment to study the effect of integrated nutrient management on okra (Abelmoschus esculentus (L.) Moench) and its residual effect on succeeding crop radish (Raphanus sativus L.) was conducted during kharif, 2004 and winter season 2004-05, respectively at the Deparment of Horticulture, College of Agriculture, Bikaner. The results revealed that application of inorganic fertilizers @ 60:30:30 kg N,P,Kq ha1 and vermicompost @ 6tha’ significantly increased the number of pickings, fruit weight, length and diameter of fruit, fruit yield/plot and fruit yield (q har’) in okra, while root length, width of root, weight of root and root yield q ha1 in succeeding crop radish.